Кардіотокографічні особливості стану плода при загрозі невиношування вагітності в II триместрі - Марченко, Н.Є. (Таврический медико-биологический вестник, 2013)
Угроза преждевременных родов характеризуется нарушениями маточно-плацентарного кровообращения и развитием дисфункции плаценты. В то же время, состояние плода оценивается по клиническим данным и результатам ультразвуковых исследований. Существуют рекомендации использовать кардиотокографический метод с 30 недель беременности. Однако КТГ-профиль в ранних сроках преждевременных родов также отображает состояние вегетативных функций, связанных с уровнем сатурации крови и аэробными процессами. Целью исследования было определение направления улучшения эффективности комплексного лечения беременных с угрозой преждевременных родов во 2-м триместре. Материалом исследований были 50 КТГ- записей беременных с угрозой преждевременных родов во 2-м триместре в сравнении с показателями 30 здоровых беременных этих же сроков. КТГ исследования проводились на мониторе типа 8030а «Hewlett Packard». Лечение женщин проводилось стандартизованными методами на основе рекомендаций клинических протоколов, Приказов МЗ Украины № 582 и 624. Установлено, что при угрозе преждевременных родов во 2-м триместре имеются отклонения от нормы здоровых беременных. Акцелерации выявлены у 46% против 82% в контрольной группе, децелерации – у 74% против 28%. Наблюдалось снижение амплитуды и частоты акцелераций. Выявлены слабые, средние и тяжелые, длительные и пикообразные децелерации. КТГ-особенности показывают риск развития дистресса плода при угрозе невынашивания беременности во II триместре. The threat of preterm labor is characterized by an impaired uteroplacental blood flow caused by an increased uterine tone and a development of the placenta dysfunction. At the same time, the assessment of the fetus is performed only with use of clinical data and ultrasound examination. The cardiotonic reflex in pregnant women appears after 30 weeks of pregnancy, hence most recommendations suggest this 30-week stage for CTG-studies and cardiotocographic (CTG) monitoring of the fetus. However, the CTG fetal profile at early terms of preterm delivery as well displays these vegetal functions directly related to the oxygen saturation of the blood and the aerobic processes. The research aim was to establish the ways of improving the efficiency of complex treatment of pregnant women with a preterm delivery threat in the second trimester, basing on the study of the CTG fetal features. The research material was the CTG recordings of 50 patients with a preterm delivery threat within the period since 22 to 28 weeks compared to the CTG recordings of 30 healthy pregnant women made at this term. The CTG recordings were made with use of the monitor 8030a «Hewlett Packard». The treatment of women with a threat of preterm delivery was performed as recommended by the clinical protocols of the Orders of the Health Ministry of Ukraine № 582 and 624. If in the second trimester there was a threat of preterm delivery, a disturbance of CTG was observed. Accelerations have been revealed in 46% of women against 82% in the control group, decelerations have been found in 74% of women against 28% in the control group. A decrease of the amplitude and frequency of acceleration, weak, middle decelerations and hard, long, and peak-shaped decelerations have been observed. The CTG characteristics show the risk of the fetal distress development in cases with a miscarriage threat in the second trimester of pregnancy.